EVALUASI KARAKTER AGRONOMI 14 VARIETAS PADI GOGO LOKAL BENGKULU - Asfaruddin; Sri Mulatsih (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
The study aimed to determine the agronomic characteristics of 14 local upland rice varieties from Bengkulu. The study used a randomized block design (RBD) with one factor, namely 14 local upland rice varieties, and six replications. It's varieties was  G1; Keleng Mano, G2; Masak Berangin, G3; Tambun Buih, G4; Sebakas, G5; Ogan, G6; Siung Kancil, G7; Sirantau, G8; Abang Pintal, G9; Babatan, G10; Komering, G11; Lampung, G12; Ir 64, G13; Sawah Darat, and G14; Umbul-umbul. The results concluded that there is agronomic diversity among the 14 local upland rice varieties from Bengkulu. The highest plant height ranged between 131 – 152 cm and was not significantly different shown in the varieties of Ogan 146.83 cm, Sirantau, Keleng Mano, Masak Berangin, Siung Kancil, Tambun Buih, Abang Pintal, Babatan, Sebakas, Komering, Lampung respectively and the lowest plant height ranged between 88 - 96 cm in the Sawah Darat, Umbul-umbul and IR 64 varieties with a height of 87.87 cm. The highest total number of tillers ranged between 15.5 – 18.5 tillers in the Sirantau variety but was not significantly different from the varieties of Ogan, Siung Kancil, IR 64, Tambun buih, Sebakas, Babatan and Lampung while the lowest number of tillers was in the Sawah Darat variety. The highest number of productive tillers ranged from 7.5 to 9.5 for the Sirantau, Komering, Ogan, Siung Kancil, IR 64, Sebakas, Tambun Buih, Lampung, Babatan, and Abang Pintal varieties. The lowest number of productive tillers ranged from 6.3 to 6.8 for the Masak Angin, Sawah Darat, Umbul-umbul, and Keleng Mano varieties. The fastest flowering time ranged from 78 to 90 days and was not significantly different for the IR 64, Umbul-umbul, Komering Lampung, and Sawah Darat varieties.